2016
DOI: 10.1093/bmb/ldw018
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic treatment of tibial eminence fracture: a systematic review of different fixation methods

Abstract: Further studies are needed to produce clear guidelines to define the best choice in terms of clinical outcomes, function and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 41 publications
2
79
0
Order By: Relevance
“…36 Finally, a systematic review by Osti et al showed that arthroscopic management reduces the risk of other complications, including postoperative pain and need for hospitalization. 55 In a more recent systematic review of pediatric tibial spine fractures, patients treated with ARIF had greater ROM deficits than those with ORIF (10.4% vs. 0%, respectively). They also had more laxity with anterior drawer and Lachman tests than ORIF patients (43.4% vs. 21.4%, respectively), but lower rates of laxity based on pivot-shift testing (13% vs. 25%, respectively).…”
Section: Arthroscopic Versus Open Approachmentioning
confidence: 98%
See 1 more Smart Citation
“…36 Finally, a systematic review by Osti et al showed that arthroscopic management reduces the risk of other complications, including postoperative pain and need for hospitalization. 55 In a more recent systematic review of pediatric tibial spine fractures, patients treated with ARIF had greater ROM deficits than those with ORIF (10.4% vs. 0%, respectively). They also had more laxity with anterior drawer and Lachman tests than ORIF patients (43.4% vs. 21.4%, respectively), but lower rates of laxity based on pivot-shift testing (13% vs. 25%, respectively).…”
Section: Arthroscopic Versus Open Approachmentioning
confidence: 98%
“…84 The systematic review by Osti et al found that cannulated screw fixation is associated with shorter postoperative immobilization and earlier return to weight-bearing than suture fixation, allowing more aggressive rehabilitation. 55 However, metal screws are commonly associated with complications in skeletally immature patients, including growth arrest, need for reoperation, and damage to the articular surface. 85,86 Headless compression screws and K-wires have been successfully reported as a solution to some of these issues, citing decreased intraarticular interference and need for hardware removal.…”
Section: Fixation Techniquesmentioning
confidence: 99%
“…Thus, it has many advantages over the other method of fixation such as screw fixation, pull out suturing. 5 This technique requires proper instrumentations and good experience in arthroscopic fixation. Once learnt, it is safe and reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…1 These injuries are commonly seen in children aged between 8-14 years and are usually sports related, however in adults these injuries are mainly related to high energy trauma usually road traffic accidents and concomitant injury to the menisci, articular cartilage, and collateral ligaments can also be seen. [2][3][4][5][6][7][8] Meyers and McKeever in 1959 described the severity of the displacement of fracture into 3 types, type I fractures have minimal or no displacement of the fragment, type II fractures have anterior one half avulsion of the eminence, but seated posterior part, and type III fractures have displaced fragment.9 Zaricznyj further modified and divided type III fractures into classes A and B, where type IIIA describes the pathology when the fragment with complete separation is displaced minimally, and type IIIB the pathology when the fragment is twisted or fragmented resulting in rotational malalignment. …”
mentioning
confidence: 99%
“…Displaced injuries of the tibial eminence may cause instability of the anterior cruciate ligament (ACL). 1 These variants of an ACL injury can occur in pediatric and adult patients; however, the mechanism is often different in the 2 populations. In children and adolescents, injury occurs as a result of a sporting injury (similar to ACL tears in skeletally mature patients), while adults tend to obtain tibial eminence fractures during high-energy trauma such as a motor vehicle accident.…”
mentioning
confidence: 99%